Influence of Standard Laboratory Procedures on Measures of Erythrocyte Damage - Wiegmann, Lena; de Zélicourt, Diane A.; Speer, Oliver; Muller, Alissa; Goede, Jeroen S.; Seifert, Burkhardt; Kurtcuoglu, Vartan (Frontiers in Physiology, 2017)
The ability to characterize the mechanical properties of erythrocytes is important in clinical and research contexts: to diagnose and monitor hematologic disorders, as well as to optimize the design of cardiovascular implants and blood circulating devices with respect to blood damage. However, investigation of red blood cell (RBC) properties generally involves preparatory and processing steps. Even though these impose mechanical stresses on cells, little is known about their impact on the final measurement results. In this study, we investigated the effect of centrifuging, vortexing, pipetting and high pressures on several markers of mechanical blood damage and RBC membrane properties. Using human venous blood, we analyzed erythrocyte damage by measuring free hemoglobin, phosphatidylserine exposure by flow cytometry, RBC deformability by ektacytometry and the parameters of a complete blood count. We observed increased levels of free hemoglobin for all tested procedures. The release of hemoglobin into plasma depended significantly on the level of stress. Elevated pressures and centrifuging also altered mean cell volume and mean corpuscular hemoglobin, suggesting changes in erythrocyte population and membrane properties. Our results show that the effects of blood handling can significantly influence erythrocyte damage metrics. Careful quantification of this influence as well as other unwanted secondary effects should thus be included in experimental protocols and accounted for in clinical laboratories.